THE EFFECT OF GIVING FERMENTATION FLOWS OF PINANG LEAF (Areca catechu L.) AND SURIAN LEAF (Toona sinensis ROXB.) ON CUPANG FISH WASH (Betta splendens Regan.) - seva miranti (Serambi Biologi, 2018)
Betta fish (Betta splendens Regan.) Is an ornamental fish that has high economic value because of the beauty of color and its fighting instincts. . However, fans of ornamental fish prefer male fish than females because male fish have better and more attractive aesthetic and color values and have higher profits. There are two non-parasitic diseases that commonly attack Betta fish, namely bite the tail and bruising. During this time the treatment used always uses chemicals such as PK solutions, methylene blue and melachite green. The use of chemicals does not always have a positive effect but can also have a negative impact on non-targeted organisms. Another effort taken to treat this disease is to use natural ingredients, namely by using fermented liquids from areca leaves and surian leaves. Medicinal plants or plants can be obtained by fermentation. Areca leaves and surian leaves are capable of producing secretions of secretive drugs. The test results of organic compounds of fermented liquid areca leaves and surian leaves containing antibiotics and other organic compounds that work synergistically accelerate healing and relieve pain or pain due to injury to the culture. This study was an experimental study, using a factorial complete randomized design consisting of two factors, namely the dosing factor (A) and the length of the observation day (B). Each treatment was repeated 6 times. Data were analyzed using Analysis Of Variants (ANOVA), the results were significantly different followed by continued testing of DNMRT level of 5%. Based on the research conducted, it can be concluded that the administration of fermented areca leaves (Areca catechu L.) and surian leaves (Toona sinensis ROXB.) Affects wound healing in Betta fish (Betta splendens Regan.) And the fastest treatment to help wound healing process that is on treatment A3 with a dose of 15 ml.